PENGEMBANGAN ALAT PERAGA 3D PADA PEMBELAJARAN IPAS MATERI GERHANA MATAHARI KELAS VI MI MIFTAHUL HUDA SEMBORO - Prayogo, Muhammad Suwignyo; Ulya, Firda Walidatul; Vina Nailiyatul; Maskur, Mohamad Ali (Abtadi : Jurnal Pendidikan Dasar, 2024)
This 3D teaching aid is a three-dimensional replica of a solar eclipse, where students can see, touch, and even directly practice how the positions of the Earth, Sun, and Moon are during a solar eclipse.   The method used in this research is R&D with the 4D model. The purpose of this research is to develop a 3D solar eclipse teaching aid for IPAS learning in the 6th grade at MI Miftahul Huda Semboro and to increase students' interest in learning. This research uses data sources from classes and students. The data collection techniques used are Observation, Interviews, Documentation, and Questionnaires. The variables used for measurement include Media and Material. The results of this study show that the validation by material experts received a score of 47 out of a maximum score of 75, with a percentage of 85.45%, which falls into the valid category. Then, the results obtained from the media expert validators were 80 out of a maximum score of 85, with a percentage of 88.89%. For the students' responses, the results obtained were a score of 80, categorized as valid. The 3D solar eclipse teaching aid will make students active during lessons. Students who were initially always sleepy in class can become enthusiastic about learning. Students' attention, which was initially scattered, can finally be focused with this teaching aid, leading to improved grades during the teaching and learning process.